TOWARDS DESIGNING AN ARTEFACT EVALUATION STRATEGY FOR HUMAN FACTORS ENGINEERING: A LEAN IMPLEMENTATION MODEL CASE STUDY - Coetzee, Rojanette (The South African Journal of Industrial Engineering, 2019)
Applying scientific methods to the evaluation of design science research artefacts is necessary to recognise the design process as design science research. Prior work has reported on this crucial evaluation component; however, limited information and guidance are available on the practices that should be followed. In this study, the framework for evaluation in design science and the elaborated action design research method in the design science research paradigm were used to develop an alternative evaluation strategy for a human factors engineering artefact. A different scientific method was used to design an evaluation episode for each of the elaborated action design research iterations: (1) a gap analysis, (2) a systematic literature review, (3) an applied thematic analysis, (4) a design requirements traceability matrix, and (5) the Delphi technique. The validity of the research design was proven using design science research guidelines, action design research principles, and a research validation matrix. This evaluation strategy indicated how the strategic use of different kinds of scientific evaluations assisted in establishing the quality of the knowledge delivered by the design science process. This study has contributed to the field of (human factor) engineering by providing a pragmatic approach to solving abstract, people-related problems in industry.